Activation of bacterial lytic polysaccharide monooxygenases with cellobiose dehydrogenase. (26th September 2016) - Loose, Jennifer S. M.; Forsberg, Zarah; Kracher, Daniel; Scheiblbrandner, Stefan; Ludwig, Roland; Eijsink, Vincent G. H.; Vaaje‐Kolstad, Gustav
Abstract: Lytic polysaccharide monooxygenases (LPMOs) represent a recent addition to the carbohydrate‐active enzymes and are classified as auxiliary activity (AA) families 9, 10, 11, and 13. LPMOs are crucial for effective degradation of recalcitrant polysaccharides like cellulose or chitin. These enzymes are copper‐dependent and utilize a redox mechanism to cleave glycosidic bonds that is dependent on molecular oxygen and an external electron donor. The electrons can be provided by various sources, such as chemical compounds (e.g., ascorbate) or by enzymes (e.g., cellobiose dehydrogenases, CDHs, from fungi). Here, we demonstrate that a fungal CDH from Myriococcum thermophilum ( Mt CDH), can act as an electron donor for bacterial family AA10 LPMOs. We show that employing an enzyme as electron donor is advantageous since this enables a kinetically controlled supply of electrons to the LPMO. The rate of chitin oxidation by CBP21 was equal to that of cosubstrate (lactose) oxidation by Mt CDH, verifying the usage of two electrons in the LPMO catalytic mechanism. Furthermore, since lactose oxidation correlates directly with the rate of LPMO catalysis, a method for indirect determination of LPMO activity is implicated. Finally, the one electron reduction of the CBP21 active site copper by Mt CDH was determined to be substantially faster than chitin oxidation by the LPMO. Overall, Mt CDH seems to be a universal electron donor for both bacterial and fungal LPMOs, indicating that their electron transfer mechanisms are similar.